Calculation of Loads and Stresses Acting on Masonry Walls - Mahmut Sami DONDUREN (International Journal of Applied Methods in Electronics and Computers, 2016)
Horizontal earthquake forces affecting the masonry walls affect the walls in the negative direction. In this study, the behaviors and types of damages of masonry constructions under the effect of earthquake are described. Moreover, the stresses in masonry construction elements were calculated by considering the reactions of masonry constructions in response to the effect of earthquakes. The construction was modelled according to the selected earthquake region. The building weight was determined according to the specified slab, hatil (vertical or horizontal RC tie members) and wall thicknesses and the earthquake loads were calculated in terms of equivalent earthquake load method. The stresses occurred in the walls against the loads were calculated and compared with allowable stress. The selected model structure was solved with FEDRA computer program. Stress distribution patterns were on the walls.